Penglipuran Village Learning Video Based on Pancasila Student Profile Effectively Improves Elementary School Students' Knowledge Competence - Metriasih, Ni Made; Agung, Anak Agung Gede; Agetania, Ni Luh Putu (International Journal of Elementary Education, 2024)
Adequate learning media facilities will support the improvement of students' knowledge competencies. Students still have difficulty in understanding the material on the Nature and Types of Norms in Society which is still lacking. This study aims to determine the feasibility and effectiveness of the Pancasila Student Profile-Based Learning Video on the Nature and Types of Norms in Society for Pancasila Subjects for Grade IV Students. This study is development research using the ADDIE development model. The data collection method uses regular multiple-choice objective tests and questionnaires and quantitative descriptive data analysis techniques and inferential statistics. The results of the study showed (1) The design of the Learning Video media with the results of the design assessment from design experts with a percentage of 90.90% which is in the qualification (Very Good). (2) The quality of the Learning Video shows the results of the expert test is very good. (3) The effectiveness of the Learning Video based on the results of the t-test obtained a t-count value (39.281) greater than the t-table (2.055) for db = 15 and a significance level of 5%, so that H0 is rejected and H1 is accepted. It was concluded that there is a significant difference before and after using learning video media based on the profile of Pancasila students on the material of the nature and types of norms in society for the Pancasila subject for grade IV elementary school students.